2022
DOI: 10.1186/s12888-021-03637-w
|View full text |Cite
|
Sign up to set email alerts
|

The new frontline: exploring the links between moral distress, moral resilience and mental health in healthcare workers during the COVID-19 pandemic

Abstract: Background Global health crises, such as the COVID-19 pandemic, confront healthcare workers (HCW) with increased exposure to potentially morally distressing events. The pandemic has provided an opportunity to explore the links between moral distress, moral resilience, and emergence of mental health symptoms in HCWs. Methods A total of 962 Canadian healthcare workers (88.4% female, 44.6 + 12.8 years old) completed an online survey during the first C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
124
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(140 citation statements)
references
References 54 publications
14
124
1
1
Order By: Relevance
“…However, the intensity (severity) of moral distress among health workers during the pandemic, in those studies that reported mean moral distress levels, has been found to be low in most [ 11 , 13 21 ] though not all [ 22 24 ] studies. Among these studies, some assessed the intensity of moral distress for specific situations [ 15 , 20 ], some assessed both the frequency and intensity of moral distress for specific situations [ 13 , 14 , 17 , 18 , 21 , 22 , 24 , 25 ] and others assessed it with a global measure of moral distress without anchoring the assessment to specific potentially-morally-distressing situations [ 11 , 19 , 23 ]. The systematic reviews by Gianetta and colleagues [ 1 ] and by Tian and colleagues [ 26 ] provide comprehensive discussions of instruments that have been used to measure moral distress.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the intensity (severity) of moral distress among health workers during the pandemic, in those studies that reported mean moral distress levels, has been found to be low in most [ 11 , 13 21 ] though not all [ 22 24 ] studies. Among these studies, some assessed the intensity of moral distress for specific situations [ 15 , 20 ], some assessed both the frequency and intensity of moral distress for specific situations [ 13 , 14 , 17 , 18 , 21 , 22 , 24 , 25 ] and others assessed it with a global measure of moral distress without anchoring the assessment to specific potentially-morally-distressing situations [ 11 , 19 , 23 ]. The systematic reviews by Gianetta and colleagues [ 1 ] and by Tian and colleagues [ 26 ] provide comprehensive discussions of instruments that have been used to measure moral distress.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have attempted to identify individual and organizational factors that are associated with moral distress during the COVID-19 pandemic because those clues may lead to interventions to prevent it or mitigate its impact. Of the studies on moral distress conducted during the COVID-19 pandemic that used standard instruments to measure moral distress [ 11 , 13 25 ], frequency of exposure to patients with COVID-19 was positively associated with moral distress [ 16 , 19 , 25 ], and adequacy of personal protective equipment [ 16 , 17 ] and a positive ethical climate in the health organization [ 17 ] was negatively associated However, the effects of other individual characteristics, such as perceived risk of developing COVID-19 or risk of dying, if infected, on moral distress are unknown as are the effects of organizational characteristics, such organizational support of their health workers and leadership communication during the pandemic. In addition, it is unknown whether punitive organizational policies during the pandemic, such as sanctioning workers who speak out about COVID-19 safety, cause moral distress.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations